Bacteremia in solid organ transplant recipients as compared to immunocompetent patients: Acute phase cytokines and outcomes in a prospective, matched cohort study. Issue 6 (20th November 2020) - Eichenberger, Emily M.; Ruffin, Felicia; Dagher, Michael; Lerebours, Reginald; Jung, Sin‐Ho; Sharma‐Kuinkel, Batu; Macintyre, Andrew N.; Thaden, Joshua T.; Sinclair, Matthew; Hale, Lauren; Kohler, Celia; Palmer, Scott M.; et al.
Abstract: We undertook a prospective, matched cohort study of patients with Staphylococcus aureus bacteremia (SAB) and gram‐negative bacteremia (GNB) to compare the characteristics, outcomes, and chemokine and cytokine response in transplant recipients to immunocompetent, nontransplant recipients. Fifty‐five transplant recipients (GNB n  = 29; SAB n  = 26) and 225 nontransplant recipients (GNB n  = 114; SAB n  = 111) were included for clinical analysis. Transplant GNB had a significantly lower incidence of septic shock than nontransplant GNB (10.3% vs 30.7%, p  = .03). Thirty‐day mortality did not differ significantly between transplant and nontransplant recipients with GNB (10.3% vs 15.8%, p  = .57) or SAB (0.0% vs 11.7%, p  = .13). Next, transplant patients were matched 1:1 with nontransplant patients for the chemokine and cytokine analysis. Five cytokines and chemokines were significantly lower in transplant GNB vs nontransplant GNB: IL‐2 (median [IQR]: 7.1 pg/ml [7.1, 7.1] vs 32.6 pg/ml [7.1, 88.0]; p  = .001), MIP‐1β (30.7 pg/ml [30.7, 30.7] vs 243.3 pg/ml [30.7, 344.4]; p  = .001), IL‐8 (32.0 pg/ml [5.6, 53.1] vs 59.1 pg/ml [39.2, 119.4]; p  = .003), IL‐15 (12.0 pg/ml [12.0, 12.0] vs 12.0 pg/ml [12.0, 126.7]; p  = .03), and IFN‐α (5.1 pg/mL [5.1, 5.1] vs 5.1 pg/ml [5.1, 26.3]; p  = .04). Regulated upon Activation, Normal T Cell Expressed and Secreted (RANTES) was higher in transplant SAB vs nontransplant SAB (mean [SD]: 750.2 pg/ml [194.6] vs 656.5 pg/ml [147.6]; p  = .046). Abstract : A prospective matched cohort study of patients with and without a solid organ transplant shows no mortality difference but a lower incidence of septic shock and lower proinflammatory cytokine levels among transplant recipients with gram‐negative but not Staphylococcus aureus bacteremia.